Current Food Security Issues: Evaluation Toolkit - Tatyana TKACHEVA; Liubov AFANASYEVA; Elizabeth TKACHEVA; Alexander PIYALTSEV (Communications of International Proceedings, 2021)
The world community is presently grappling with the problem of ensuring global and national food security. Under conditions of increasing international political tension, military conflicts in different parts of the globe, the pandemic, connected with spreading of coronavirus infection, the problem of food security has aggravated both in the country as a whole, and in regions, in particular, and demands urgent decision. The food security dynamics in the Russian Federation have been assessed based on the data of the Global Food Security Index. The study of the dynamics of basic foodstuffs sales by agricultural organizations in the Russian Federation and the reduction of food expenditures in the structure of consumer spending of households has led to the conclusion that the Russian population has sufficient physical and economic access to safe and nutritious food that meets their dietary needs and food preferences in order to maintain an active and healthy lifestyle.
Keywords: Food Security; Food Security Level; Food Resources; Population Income; Quality of Life.